Leveraging 'golden-hour' WUE for developing superior vegetable varieties with optimal water-saving and growth traits - Rujia Jiang; Ting Sun; Zheng Shi; Menachem Moshelion; Pei Xu (Vegetable Research)
Creating high-yielding and water-efficient crop varieties relies on a profound understanding of crop water usage and photosynthetic physiology. Currently, the prevailing strategies for improving drought response in crops center around the regulation of stomata. However, while reducing stomatal conductance can boost water use efficiency (WUE), it results in a decline in photosynthetic assimilation capacity, because stomata function as a shared conduit for both CO2 intake and water evaporation. With the advancement of phenomics, recent research has unveiled disparities in the regulatory patterns of photosynthesis and transpiration (Tr) in plants. Depending on the genotype, the early morning period, when light intensity is sufficient yet vapor pressure deficit (VPD) is low, is referred to as the 'golden hours' for high water use efficiency (WUE). During this window, plants can attain higher photosynthetic intensity with lower Tr levels in a low VPD environment. This is highly advantageous for efficient biomass production under water-saving conditions. Thus, precise and more judicious modulation of WUE through stomatal control becomes pivotal in addressing the delicate balance between water conservation and yield. This perspective paper introduces the concept and significance of the golden-hour WUE (GHW) trait and elucidates the methods for quantitative and high-throughput screening of this trait using modern phenotyping techniques. Building upon this foundation, a systematic approach for screening and leveraging the GHW traits in plant breeding is proposed. This proposed approach holds the potential to offer a solution for achieving a balance between water-saving and plant growth.